A corpus study of splitting and joining sentences in translation. Issue 1 (April 2019) - Frankenberg-Garcia, Ana
Abstract : The use of corpora in translation studies has risen dramatically over recent years, contributing towards a growing body of empirical research focussing not only on what differentiates translated from non-translated language, but also on the changes or shifts that translators make from source to target texts. Most of these studies are centred on sub-sentential elements, such as the contrastive use of particular lexis or grammar. However, translation shifts can transcend the level of the sentence. For example, sentences can be split or joined in translation, or there can be complex shifts that combine the two. While there is some research on sentence splitting, there do not seem to be many studies about sentence joining, or indeed sentence splitting and joining together. This study seeks to address this gap. Using a bi-directional parallel corpus of Portuguese and English fiction, over 90, 000 source-text sentences and their corresponding text in translation were analysed from a quantitative perspective, and a closer look was taken at a sample of over 1, 000 parallel text segments involving sentence joining and splitting. The main findings were that in both translation directions ( 1 ) there was a strong tendency for sentence preservation, ( 2 ) the differences between sentence splitting and joining were not significant, and ( 3 ) changes in sentence boundaries were predominantly associated with the standardisation or normalisation of syntax and a tendency for explicitation.